Pregabalin enhances myelin repair and attenuates glial activation in lysolecithin-induced demyelination model of rat optic chiasm. (6th March 2017) - Daneshdoust, Danyal; Khalili-Fomeshi, Mohsen; Ghasemi-Kasman, Maryam; Ghorbanian, Davoud; Hashemian, Mona; Gholami, Mohammad; Moghadamnia, Aliakbar; Shojaei, Amir
Graphical abstract: Highlights: Pregabalin decreases latency of VEP waves following LPC injection. Pregabalin enhances myelin repair of optic chiasm following LPC injection. Pregabalin attenuates glial activation in optic chiasm after injection of LPC. Abstract: Multiple sclerosis (MS) is an autoimmune disease in which more than 70% of patients experience visual disturbance as the earliest symptoms. Lysolecithin (LPC)-induced focal demyelination model has been developed to evaluate the effects of different therapies on myelin repair improvement. In this study, the effects of pregabalin administration on myelin repair and glial activation were investigated. Local demyelination was induced by administration of LPC (1%, 2 μL) into the rat optic chiasm. Rats underwent daily injection of pregabalin (30 mg/kg, i.p) or vehicle. Visual-evoked potentials (VEPs) recordings were performed for evaluating the function of optic pathway on days 3, 7, 14 and 28 post lesions. Myelin specific staining and immunostaining against GFAP and Iba1 were also carried out for assessment of myelination and glial activation respectively. Electrophysiological data indicated that pregabalin administration could significantly reduce the P1-N1 latency and increase the amplitude of VEPs waves compared to saline group. Luxol fast blue staining and immunostaining against PLP, as mature myelin marker, showed that myelin repair was improved in animals received pregabalin treatment. In addition, pregabalin effectively reduced the expression of GFAP and Iba1 as activated glial markers in optic chiasm. The present study indicates that pregabalin administration enhances myelin repair and ameliorates glial activation of optic chiasm following local injection of LPC.